The Effect of Digital Marketing Training on The Digital Marketing Skills of Orphanage Business Unit Managers in Surabaya - Saifuddin, Muchammad; Wicaksono, Rianto Anugerah; Gangsar Ramadanti, Firda (Jurnal Manajemen dan Inovasi (MANOVA), 2025)
Objective – This study aims to test the effect of digital marketing training on the digital marketing skills of orphanage business unit administrators in Surabaya. Design/methodology/approach – Using a quantitative approach, this study applies an experimental design with a pre-test and post-test model on 25 respondents. The variables studied are digital marketing skills as measured by cost indicators, incentive programs, website design, and interactivity. Findings – The results of the study showed a significant difference in the digital marketing skills of orphanage administrators before and after training. Digital marketing training has been shown to significantly improve participants' skills. Research limitations/implications – This study was only conducted in Surabaya. Therefore, it is recommended to conduct further studies in the same context in other areas in Indonesia or other countries. The researcher also suggests exploring other variables that may affect digital marketing skills. Practical implications – This study encourages orphanages to implement effective digital marketing training, so that they can increase financial independence through their business units. The importance of this training can be a reference for other orphanages in developing more modern marketing strategies. Originality/value – This study provides new insights into the impact of digital marketing training in the context of orphanages, which is rarely discussed in the literature. The originality of this study lies in its focus on orphanage administrators and the digital marketing skills relevant to the sustainability of their business units.